Dedicated Individuals who Motivate the Development of International Law and the Obligation to “Prevent” Crimes Against Humanity - Jennifer Trahan (Washington University Global Studies Law Review, 2022)
In honoring Professor Leila N. Sadat, this essay will address two related topics. First, it considers how the international community or a large organization such as the United Nations can be “moved” toward the development of international law, and reflects on the importance of dedicated individuals, such as Professor Sadat, in contributing toward such momentum. Second, it examines the importance of concluding a crimes against humanity convention—a project to which Professor Sadat has devoted many years. Specifically, it looks at the divisive debate that has periodically occurred as to whether crimes constitute “genocide” or not, while time and lives are lost, with the resulting consequence often being inaction by states. While having a convention cannot alone create the political “will” to act, it could at least provide a clear legal framework, including the obligation to “prevent” crimes against humanity, which would then parallel the obligation to “prevent” genocide found in the Genocide Convention. That legal development could contribute to avoiding paralysis by states that mistakenly appear to perceive a duty to act to stop crimes only if they constitute genocide.